The Queer-Cyberspace of Jeanette Winterson's' The Powerbook: A Critique of St. Augustine's Metaphysical Philosophy. Issue 3 (27th May 2022) - Karadas, Firat
ABSTRACT: Jeanette Winterson's The PowerBook is about the cyber and story-making experience of Ali/Alix, the main character and the narrator of many interwoven narratives who experiments with time and retells well-known historical literary texts in the novel. Toward the end of the novel, while he knots himself into time, Ali calls to mind St. Augustine and thinks that St. Augustine might be right when he said "the universe was not created in time but with time." St. Augustine, one of the most important Fathers of Christianity whose writings had a great impact on shaping the Western prejudices about sex and the body, is also important for his ideas of time. In spite of the short reference to St. Augustine in The PowerBook, Ali/Alix's story-telling experience can be read not only as a deconstruction and encarnalization of St Augustine's metaphysical philosophy, but also as reconstructing his personal life and philosophy in the queer spatio-temporal cyber world of the novel.